FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESEHATAN PADA PEKERJA DI TOKO PERTANIAN KECAMATAN PASAR KOTA JAMBI TAHUN 2022 - Rahmadani Rahmadani; Melda Yenni; T. Samsul Hilal (Jurnal Cakrawala Ilmiah, 2023)
Pesticides are generally toxic materials that need to be managed properly not only for farmers, but also for people who work in pesticide kiosks. Health problems due to pesticides can be caused by inappropriate pesticide management behavior, psychosocial factors and not using PPE. The agricultural shop in Market District, Jambi City is the center of the agricultural shop in Jambi Province. The health problems experienced by these workers are headache/dizziness, nausea, excessive sweating, shortness of breath, and muscle aches. The purpose of this study was to determine factors related to health in workers in the Agricultural Shop. This research is a quantitative study using a cross sectional design. This research was conducted in the Market District of Jambi City in July 2022. The sample of the study was farmer shop workers in the Market District of Jambi City with a total sample of 30 people. Sampling technique using total sampling technique. The research instrument is a questionnaire. Data were analyzed using chi square statistical test. A total of 56.7% of respondents have health complaints, 40.0% of respondents have poor psychosocial behavior, 40.0% of respondents have poor pesticide management and 53.3% of respondents are not good at using PPE. The bivariate results showed that there was a relationship between psychosocial (p=0.042), pesticide management (p=0.005) and the use of PPE (p=0.001) with the health of workers at the Farm Shop, Market District, Jambi City in 2022. It is expected that workers always use PPE when working. Shop owners are expected to always remind workers to use PPE.